Impact of coil price knowledge by the operator on the cost of aneurysm coiling. A single center study. (15th September 2017) - Finitsis, Stephanos; Fahed, Robert; Gaulin, Ian; Roy, Daniel; Weill, Alain
Abstract : Background: Endovascular treatment of aneurysms with coils is among the most frequent treatments in interventional neuroradiology, and represents an important expense. Each manufacturer has created several types of coils, with prices varying among brands and coil types. The objective of this study was to assess the impact of cost awareness of the exact price of each coil by the operating physician on the total cost of aneurysm coiling. Materials and methods: This was a comparative study conducted over 1 year in a single tertiary care center. The reference cohort and the experimental cohort consisted of all aneurysm embolization procedures performed during the first 6 months and the last 6 months, respectively. During the second period, physicians were given an information sheet with the prices of all available coils and were requested to look at the sheet during each procedure with the instruction to try to reduce the total cost of the coils used. Expenses related to the coiling procedures during each period were compared. Results: 77 aneurysms (39 ruptured) in the reference cohort and 73 aneurysms (36 ruptured) in the experimental cohort were treated, respectively. There was no statistically significant difference regarding aneurysm location and mean size. The overall cost of the coiling procedures, the mean number of coils used per procedure, and the median cost of each procedure did not differ significantly between the two cohorts. Conclusion: Awareness of the precise price of coils by operators without any additional measure did not have a scientifically proven impact on the cost of aneurysm embolization.